2015
DOI: 10.2147/jpr.s55586
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the clinical significance of functional pain syndromes in children

Abstract: Functional pain syndromes (FPS) characterize a subset of individuals who experience pain and related symptoms and disability without clear structural or disease etiology. In the pediatric population, FPS hold high clinical importance due to significant prevalence rates and potential to persist into adulthood. Although extensive research has been executed to disambiguate FPS, the syndromes that fall within its spectrum remain conceptually complex and sometimes ill-defined. This paper provides an overview of ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…This is especially relevant to those suffering from chronic pain, as the pain often emerges despite seemingly normal biological functioning. The biomedical model has now largely been replaced with a biopsychosocial model, which incorporates all of the aspects in a patient’s life that converge and potentially maintain a cycle of pain [21]. This has been determined to be a more effective conceptual and theoretical stance as it is suggested that pain cognitions are not only associated pain intensity, but may also be barriers to effective treatment if left unaddressed [22].…”
Section: Overview Of Pain Neuroscience Educationmentioning
confidence: 99%
“…This is especially relevant to those suffering from chronic pain, as the pain often emerges despite seemingly normal biological functioning. The biomedical model has now largely been replaced with a biopsychosocial model, which incorporates all of the aspects in a patient’s life that converge and potentially maintain a cycle of pain [21]. This has been determined to be a more effective conceptual and theoretical stance as it is suggested that pain cognitions are not only associated pain intensity, but may also be barriers to effective treatment if left unaddressed [22].…”
Section: Overview Of Pain Neuroscience Educationmentioning
confidence: 99%
“…Somatic symptoms and negative emotional reactivity have been associated with adverse psychological and social consequences in adolescence, including absence from school, reduced academic achievement, and impaired work ability (Basch et al, 2015 ; Winding & Andersen, 2019 ). These consequences provide insights into the current findings, that they also predict adult health and wellbeing in early adulthood and middle adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic conceptualization of pediatric chronic pain is often formulated using the BPS model of pain. 4 , 35 This model asserts that pain chronicity occurs because of the interaction between central sensitization or centralization of pain and HPA axis hyperactivity, in conjunction with psychological (eg, anxiety, depression, pain catastrophizing, and fear of pain) and social (eg, decreased social engagement and school attendance) factors contributing to functional disability and, in turn, pain chronicity. 34 , 35 The pain feedback loop is exacerbated by these sociobiological loads, producing a failure of homeostasis and increased allostatic load (AL), ie, wear and tear on regulatory systems, including the nervous system, in response to repeated or prolonged stress.…”
Section: Neurobiological Underpinnings Of Pain and Potential Targets Of Interventionmentioning
confidence: 99%